Genetics of human isolated hereditary nail disorders. (8th September 2015) - Khan, S.; Basit, S.; Habib, R.; Kamal, A.; Muhammad, N.; Ahmad, W.
Summary: Human hereditary nail disorders constitute a rare and heterogeneous group of ectodermal dysplasias. They occur as isolated and/or syndromic ectodermal conditions where other ectodermal appendages are also involved, and can occur associated with skeletal dysplasia. 'Nail disorder, nonsyndromic congenital' (OMIM; Online Mendelian Inheritance in Man) is subclassified into 10 different types. The underlying genes identified thus far are expressed in the nail bed and play important roles in nail development and morphogenesis. Here, we review the current literature on nail disorders and present a coherent review on the genetics of nail disorders. This review will pave the way to identifying putative genes and pathways involved in nail development and morphogenesis. Abstract : Linked Comment: Betz, Br J Dermatol 2015; 173: 886 .